Futurity of Aritificial Intelligence on Remote Monitoring of Patients in E-Healthcare Through Cloud Computing - Ezhilarasi. M; Ajith.S; Vigneshwaran.L.V; M, Senthil Kumar. (Journal of Biomedical and Pharmaceutical Research, 2022)
People’s health is becoming increasingly crucial to track in this ’New Normal’ post-COVID-19 modern environment. The need of the hour is for modern technology that uses sensory sensors to track and record critical characteristics while also communicating with others. Keeping track of all of the medical factors is difficult. Collecting post-operative data of persons with non-communicable disorders such as diabetes and heart disease on a regular basis on an ongoing basis The technology we’re talking about is intended for those who are confined to their homes. Especially when leaving the house and being exposed to the outside world is forbidden. This paper made a recommendation. For obtaining patient data, a breakthrough health management system based on the Internet of Things (IoT) has been developed. medical characteristics in both urban and rural settings. Keywords: Remote patient monitoring(RMP) , healthcare delivery, e-health arctitechure, telemedicine.